Implementing the School Literacy Movement in IPAS (Integrated Science) Learning under the Merdeka Curriculum: A Case Study in an Indonesian Elementary School - Myrtawati Myrtawati; Akbar Al Masjid; Ana Fitrotun Nisa; Berliana Heni Cahyani; Elyas Djufri (MASI Mandiri Edukasi, 2026)
A low literacy culture among Indonesian elementary students severely hampers reading comprehension and science learning outcomes in the Integrated Natural and Social Sciences (IPAS) subject under the Merdeka Curriculum. This descriptive qualitative study, using naturalistic inquiry, examines the implementation of the School Literacy Movement (GLS) in fourth-grade IPAS learning at SD Negeri Mutihan, Bantul, Yogyakarta. The main aim was to describe GLS practices, identify supporting/inhibiting factors, and formulate teacher strategies addressing literacy barriers. Purposive sampling included one principal, one fourth-grade teacher, and five students representing diverse reading abilities. Data were collected through classroom observations (3 sessions), semi-structured interviews (60-90 minutes each), and documentation analysis (lesson plans, literacy records). Interactive qualitative analysis followed Miles & Huberman's model: data reduction (coding), display (thematic matrices), and conclusion drawing (pattern verification). Triangulation ensured credibility via source, method, and time comparisons. Key findings revealed: (1) systematic 15-minute reading routines and contextual IPAS texts integration; (2) reading corners utilization despite gadget distractions; (3) low student motivation as the primary barrier countered by teacher-led creative literacy activities; (4) policy-teacher-family synergy essential for sustainability. Schools should prioritize literacy-rich IPAS environments through teacher training, parental engagement programs, and diverse science reading materials to enhance outcomes of the Merdeka Curriculum.